The robust uncapacitated multiple allocation p-hub median problem. (August 2017) - Talbi, El-Ghazali; Todosijević, Raca
Highlights: The robust uncapacitated multiple allocation p-hub median problem studied. A new more general robustness measure introduced. Extensive testing performed to indicate advantages of the newly proposed measure. Solutions obtained under different uncertain settings compared. Abstract: In this paper we study the uncapacitated multiple allocation p-hub median problem and propose several ways to deal with the uncertainty that may occur in the flow. More precisely, the paper introduces a new way to quantify the robustness of a solution in the presence of uncertainities. The main characteristic of the newly proposed robustness measure is its ability to provide a solution which is robust for any realization of the number of changes that may occur. An extensive empirical study is conducted to justify the need for the new robustness measure as well as the potential gains it brings.